Antiviral activity of Vigna radiata extract against feline coronavirus in vitro - Ai-Ai Chou; Chung-Hui Lin; Yen-Chen Chang; Hui-Wen Chang; Yi-Chen Lin; Chia-Chen Pi; Yao-Ming Kan; Hao-Fen Chuang; Hui-Wen Chen (Veterinary Quarterly)
Feline infectious peritonitis (FIP) is a fatal illness caused by a mutated feline coronavirus (FCoV). This disease is characterized by its complexity, resulting from systemic infection, antibody-dependent enhancement (ADE), and challenges in accessing effective therapeutics. Extract derived from Vigna radiata (L.) R. Wilczek (VRE) exhibits various pharmacological effects, including antiviral activity. This study aimed to investigate the antiviral potential of VRE against FCoV, addressing the urgent need to advance the treatment of FIP. We explored the anti-FCoV activity, antiviral mechanism, and combinational application of VRE by means of in vitro antiviral assays. Our findings reveal that VRE effectively inhibited the cytopathic effect induced by FCoV, reduced viral proliferation, and downregulated spike protein expression. Moreover, VRE blocked FCoV in the early and late infection stages and was effective under in vitro ADE infection. Notably, when combined with VRE, the polymerase inhibitor GS-441524 or protease inhibitor GC376 suppressed FCoV more effectively than monotherapy. In conclusion, this study characterizes the antiviral property of VRE against FCoV in vitro, and VRE possesses therapeutic potential for FCoV treatment.